PVD growth of spiral pyramid-shaped WS2 on SiO2/Si driven by screw dislocations - Yassine Madoune; DingBang Yang; Yameen Ahmed; Mansour M. Al-Makeen; Han Huang (Frontiers in Chemistry, 2023)
Atomically thin layered transition metal dichalcogenides (TMDs), such as MoS2 and WS2, have been getting much attention recently due to their interesting electronic and optoelectronic properties. Especially, spiral TMDs provide a variety of candidates for examining the light-matter interaction resulting from the broken inversion symmetry, as well as the potential new utilization in functional optoelectronic, electromagnetic and nanoelectronics devices. To realize their potential device applications, it is desirable to achieve controlled growth of these layered nanomaterials with a tunable stacking. Here, we demonstrate the Physical Vapor Deposition (PVD) growth of spiral pyramid-shaped WS2 with ∼200 μm in size and the interesting optical properties via AFM and Raman spectroscopy. By controlling the precursors concentration and changing the initial nucleation rates in PVD growth, WS2 in different nanoarchitectures can be obtained. We discuss the growth mechanism for these spiral-patterned WS2 nanostructures based on the screw dislocations. This study provides a simple, scalable approach of screw dislocation-driven (SDD) growth of distinct TMD nanostructures with varying morphologies, and stacking.